EXCELLENCE ADMINISTRATION FOR OFFICE OF THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE SURATTHANI CHUMPHON - Krabin, Benchamat; Jirarotephinyo, Nitwadee; Tipnak, Peerapong (Journal of MCU Nakhondhat, 2023)
The objective of this article research were: 1) To study the management components for excellence administration under Office of the Secondary Education Service Area, Suratthani, Chumphon. 2) To examine the management components for excellence administration under Office of the Secondary Education Service Area, Suratthani, Chumphon. This research was mixed research with qualitative and quantitative research. Population: School Administrators under Office of the Secondary Education Service Area, Suratthani, Chumphon from 66 schools, there were 264 administrators and 2,417 teachers, totaling 2,681 people. Surat Thani Province and Chumphon Province as a noble and calculated by the sample size determination formula of Krejcie & Morgan. There were 471 samples used in this research. The research tools were semi-structured interviews, questionnaires, and focus group discussions. Statistics used in data analysis were frequency, percentage, mean, standard deviation, Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA). The findings were revealed as follows: 1) Administrative Components for Educational Institution Excellence under Office of the Secondary Education Service Area, Suratthani, Chumphon, consisting of 6 components: 1) Learner Quality 2) Curriculum Administration, 3) Administration, 4) Relationship between Schools, Parents and Communities, 5) Personnel and Personnel Management, and 6) Excellence of Educational Institutes. 2) The results of the research revealed that (1) the administrative components for educational institute excellence Under the Surat Thani Secondary Educational Service Area Office, Chumphon, consisted of 6 components: 1) learner quality 2) curriculum administration, 3) management, 4) relationship between schools, parents and communities, 5) personnel and personnel management, and 6) Excellence of Educational Institutions (2) Elements of the Management Model for Excellence for Educational Institutions Under the Secondary Educational Service Area Office, Surat Thani, Chumphon, are consistent with the empirical data. and from group conversations. Most of the experts agreed that the order of the new components should be modified to be as follows: 1) School excellence 2) Relationship between schools, parents, and communities 3) School curriculum administration 4) Management 5) personnel and personnel management, and 6) learner quality.